The Effect of Individual and Cooperative Learning on Students’ Writing Ability - Ishak Ishak; Euis Yanah Mulyanah (Journal of English Language Studies, 2017)
The objectives of the research are to improve students’ writing ability and to enrich the effective approach for the students in improving their writing ability. This is an experimental study conducted at Muhammadiyah University of Tangerang.  The data were collected from 46 students as sample from 3rd semester at Muhammadiyah University of Tangerang and they were divided into two classes, one class as the experiment group and the other one as the control group. The researcher used quasi experimental research design to get the data and the data are gathered through pretest and posttest of writing by using writing essay as the instrument of the research. Based on the result of t-test shows that tobserved (1.93) > (1.72) ttable. So, Ho was rejected and Ha was accepted. Mean that, teaching writing by using cooperative learning technique was more effective than teaching writing using individual learning.  In teaching writing, it is advisable for lecturers to learn the approach of cooperative and individual learning, but the lecturer should facilitate cooperative learning because it makes the students more motivated in the learning process. Keywords: Individual, Cooperative Learning, Writing Ability